SWOT ANALYSIS DEVELOPMENT OF BATIK BANTUL - Sri Suryaningsum (Universitas Mercu Buana, 2019)
This research focuses on the development of Batik Bantul using SWOT analysis. SWOT analysis is a comprehensive review of the strengths, weaknesses, opportunities, and threats of a company. This analysis is needed to determine several strategies that must be applied to a company. Seeing the development of batik that is getting better and more in demand by tourists, the analysis to determine business strategies is of particular concern to the company. Not only the quality of the product in the spotlight, but the promotion and placement (location) of product sales. With the opportunity to increase sales at existing tourist attractions, accompanied by threats from external companies. The threat comes from other companies that present the same product at a price below the price offered by Batik Bantul craftsmen. This SWOT analysis is expected to be able to overcome the existing threats. In addition to threats and opportunities, companies must also analyze the advantages and disadvantages. The advantages possessed are used as weapons to compete in market share. While the disadvantages can be used as guidelines to improve in terms of quality, both from natural resources and human resources that exist in the company.